How longitudinal observational studies can guide screening strategy for rare diseases. Issue 5 (10th May 2022) - Mütze, Ulrike; Mengler, Katharina; Boy, Nikolas; Gleich, Florian; Opladen, Thomas; Garbade, Sven F.; Kölker, Stefan
Abstract: Newborn screening (NBS) is an important secondary prevention program, aiming to shift the paradigm of medicine to the pre‐clinical stage of a disease. Starting more than 50 years ago, technical advances, such as tandem mass spectrometry (MS/MS), paved the way to a continuous extension of NBS programs. However, formal evidence of the long‐term clinical benefits in large cohorts and cost‐effectiveness of extended NBS programs is still scarce. Although published studies confirmed important benefits of NBS programs, it also unraveled a significant number of limitations. These include an incompletely understood natural history and phenotypic diversity of some screened diseases, unreliable early and precise prediction of individual disease severity, uncertainty about case definition, risk stratification, and indication to treat, resulting in a diagnostic and treatment dilemma in individuals with ambiguous screening and confirmatory test results. Interoperable patient registries are multi‐purpose tools that could help to close the current knowledge gaps and to inform further optimization of NBS strategy. Standing at the edge of introducing high throughput genetic technologies to NBS programs with the opportunity to massively extend NBS programs and with the risk of aggravating current limitations of NBS programs, it seems overdue to include mandatory long‐term follow‐up of NBS cohorts into the list of screening principles and to build an international collaborative framework that enables data collection and exchange in a protected environment, integrating the perspectives of patients, families, and the society. Abstract :